Faktor-Faktor Penentu Tingkat Kemiskinan di Kabupaten Bantul - Azizah Kurniasih; Jaka Sriyana (Unisia, 2012)
This research is designated to discover how education, unemployment and health influence the poverty with particular reference to the Province of Jogjakarta. Poverty is a complicated problem which involve other various aspects and hence the solution for such problem can not be taken separately among those problems. Poverty link to the low income, illiteracy, and other various problems. Especially in BantuI regency, problem of poverty is relatively high, this can be seen that there are 15 undeveloped villages within 17 sub regencies. The research shows that that the variable of education positively, though not significantly affect the level of poverty. Again, the variable of unemployment also affect positively and significantly the level of poverty. And it is also proven that the healthiness negatively but significant affects the level of poverty.Key words: education, unemployment, healthiness, poverty